Temperature-dependent raman spectroscopy of titanium trisulfide (TiS3) nanoribbons and nanosheets - Pawbake, Amit S.; Island, Joshua O.; Flores, Eduardo; Ramon Ares, Jose; Sanchez, Carlos; Ferrer, Isabel J.; Jadkar, Sandesh R.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2015)
Titanium trisulfide (TiS3) has recently attracted the interest of the 2D community because it presents a direct bandgap of similar to 1.0 eV, shows remarkable photoresponse, and has a predicted carrier mobility up to 10000 cm(2) V-1 s(-1). However, a study of the vibrational properties of TiS3, relevant to understanding the electron-phonon interaction that can be the main mechanism limiting the charge carrier mobility, is still lacking. In this work, we take the first steps to study the vibrational properties of TiS3 through temperature-dependent Raman spectroscopy measurements of TiS3 nanoribbons and nanosheets. Our investigation shows that all the Raman modes linearly soften (red shift) as the temperature increases from 88 to 570 K due to anharmonic vibrations of the lattice, which also includes contributions from the lattice thermal expansion. This softening with the temperature of the TiS3 modes is more pronounced than that observed in other 2D semiconductors, such as MoS2, MoSe2, WSe2, and black phosphorus (BP). This marked temperature dependence of the Raman spectra could be exploited to determine the temperature of TiS3 nanodevices by using Raman spectroscopy as a noninvasive and local thermal probe. Interestingly, the TiS3 nanosheets show a stronger temperature dependence of the Raman modes than the nanoribbons, which we attribute to lower interlayer coupling in the nanosheets.
Keywords: 2D semiconductors; layered materials; Raman spectroscopy; thermal effect; TiS3 nanoribbons; TiS3 nanosheets

Temperature dependent raman spectroscopy and sensing behavior of few layer SnSe2nanosheets - Pawbake, Amit S.; Date, Abhijit; Jadkar, Sandesh R.; Late, Dattatray J. (Chemistryselect, 2016)
Two- dimensional (2D) tin diselenide (SnSe2) nanosheets were synthesized using solvothermal route in one step and perform its humidity sensing, photo sensing and temperature dependant Raman spectroscopy studies. The sensor devices based on few layer SnSe2 nanosheets were prepared and which shows fast response as well as recovery time along with good long-term stability and high sensitivity. The photo sensing behavior shows the typical response time and recovery time to be similar to 310 ms and similar to 340 ms respectively for visible light illumination. The room temperature humidity sensing behaviors were studied in the range of 11-97% relative humidity (RH). The ob-served sensitivity of similar to 81% with response time of similar to 74 sec and recovery time of similar to 30 sec were calculated for the few layer SnSe2 nanosheets based humidity sensor. The humidity sensing results confirms the high stability of the device even after six months of time. The temperature dependent Raman spectroscopy investigation in the range of 80 K to 593 K were carried out which shows the negative temperature coefficient and softening of Raman modes as we increases the temperature. The softening modes of SnSe2 nanosheets due to temperature were explained on the basis of a double resonance process which is more active in an atomically thin sample.

Temperature dependent Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets - Pawbake, Amit S.; Erande, Manisha B.; Jadkar, Sandesh R.; Late, Dattatray J. (RSC Advances, 2016)
The present investigation deals with temperature dependant Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets. The temperature dependent study illustrates that softening of the A(g)(1), B-2g and A(g)(2) modes occurs as the temperature increases from 78 K to 573 K. The calculated temperature coefficients for the A(g)(1), B-2g and A(g)(2) modes were found to be -0.028 cm(-1) K-1, -0.028 cm(-1) K-1 and -0.018 cm(-1) K-1 respectively. The observed phenomenon can be utilized for characterizing other emerging two-dimensional inorganic layered materials with atomic thickness.